Extended warranty and its impact on perception in sales promotion of durables - Dunković, Dario; Knežević, Blaženka (Business, Management and Economics Engineering, 2023)
Purpose – The aim of the paper is to determine the perception of extended warranty when communicated by retailer during the sales promotion of durable products (e.g. refrigerators). We consider perception as five signals or conceptual dimensions in retail context. The research question is: What perception creates the extended warranty? The dimensions studied can increase or decrease the value and therefore attractiveness of the product. In this sense, extended warranties are a tool that retailers can use to change customers’ attitudes towards a product. There is little primary research that shows how communication of extended warranties influences customer perception and which signals are relevant to customers and retailers. Research methodology – A survey was conducted on a sample of 180 respondents. The measurement model includes extended warranty as a construct with five observed variables related to customer sentiment (risk relief, no cost, quality, price and brand). Each sentiment signal is tested as a separate hypothesis. The model was tested with SEM and CFA was used to interpret the data. Findings – In advertising theory, the extended warranty is seen as a signal of better quality and reliability, but we have shown that it creates a sense of risk relief in the purchase decision. Research limitations – Extended warranties can give rise to perceptions other than those examined in the measurement model. For different categories of consumer goods, the warranty features can be perceived differently. Practical implications – Retailers design promotional activities by communicating extended warranty to customers. As a result, they do not perceive promoted object as a more expensive due to warranty provision, even though it offers value to customers. Originality/Value – The originality of the article lies in the different perceptions that arise when customers are confronted with an extended warranty as part of the product promotion in a store. The empirical model proposes a construct of perception of the extended warranty mediated by a unique combination of signals such as risk relief, no cost sentiment, quality, price, and brand value. Only two signals, namely risk relief and quality, influence purchase intention.